Comportamento tribológico dos compósitos poliméricos utilizados no anel de atrito do amortecedor torcional de discos de embreagem - Rosa, Avital Gabriel de Almeida (2017)
The three cylinder motors tend to vibrate more than the conventional four cylinder ones. In this new condition the transmission system and in particular the torsional damper of the clutch disc is subjected to sever wear and friction. The great challenge is to select new materials with low wear rate and adequate friction coefficient to attenuate this new vibration level. In this work three different candidate materials to be used as friction rings inside the torsional damper of clutch discs were tested in terms of wear resistance and friction. Two of the studied materials are currently used in the market (PA66 35 GF and NBR) in four cylinder motors and the third is currently used in clutch facing (NBR matrix composite). The materials were purchased from Schaeffler suppliers. The first step was the microstructural characterization and determination of the thermal stability of the three materials without the influence of friction. For that, the microstructure was analyzed by optical and electronic microscopy of Scanning (SEM), the amount of fibers and inorganic reinforcers was determined by burning tests and,the transition temperatures were determined by differential calorimetry. Two aging temperatures were studied 80 and 150oC. The effect of the ageing time was determined by hardness and infrared spectroscopy measurements. Among the three materials and clutch facing, they show a more stable structure in the temperature range between 80 and 150ºC. The PA66GF35 suffered changes in crystalline content and the NBR thermal degradation. The second step consisted in determining the wear characteristics of the material in bench tests with the objective of measuring the wear rate and friction coefficient of the material under extreme conditions of specific pressure and velocity (DIN50320, 1979). The results of the friction test had the following classification: NBR (0.13)> PA66GF35 (0.11)> clutch facing (0.09). Despite having a lower coefficient of friction, the clutch facing was the only material that achieved the minimum wear resistance required for the friction ring. Therefore the clutch facing is the best material for a 3 cylinder engine that requires a higher wear and thermal resistance on the clutch plate.